Trends and influencing factors of self-management in patients with chronic heart failure: a longitudinal study - Wen Ding; Jingyu Lu; Fei Wang; Ling Bai; Juan Liu; Ru Wang (BMC Geriatrics)
Abstract Background Good self-management behaviors can improve the physical function and quality of life of patients with heart failure and reduce hospitalization, mortality, and medical expenses. While the overall self-management level among patients with chronic heart failure (CHF) in China is low, previous studies have often used a cross-sectional design, and few have followed up on patients’ self-management beyond 6 months after discharge. This study aimed to explore the factors influencing and the changes in the self-management level of patients with CHF and provide a basis for the timing and choice of interventions within 1 year after discharge. Methods A longitudinal study was conducted from December 2021 to June 2022, including patients with CHF who met all the inclusion criteria. Data on demographics, disease-related details, social support, self-efficacy, and other information were collected during hospitalization (T0) and reevaluated at 1 month (T1), 3 months (T2), 6 months (T3), and 12 months (T4) after discharge. Results A total of 213 patients were enrolled at T0, with 206, 201, 189, and 173 patients completing follow-up at T1, T2, T3, and T4, respectively. The self-management score was lowest at T0, highest at T1, began to decline at T2, and stabilized at T3; however, T3 remained higher than T0. Social support, self-efficacy, disease course, medication type, education level, and personal monthly income were identified as factors influencing self-management. Conclusions The study findings indicate that self-management is a dynamic process of change. The level of self-management was at a high level 3 months after the patients were discharged from the hospital, but showed a decreasing trend from 6 months, which was related to numerous factors. This study helps to provide a theoretical basis for the timing and content of self-management intervention for patients with CHF by clinical healthcare professionals.